Situating Cyberzone: Black lesbian identity in comics. Issue 4 (2nd October 2018) - Howard, Sheena C.
ABSTRACT: Cyberzone is a fitting place to start any discussion around Black lesbian identity in comics, as it is the first comic book that this researcher could find which features a Black lesbian female lead superheroine. Cyberzone was self-published by Jimmie Robinson in 1994 and later re-vamped into a mini-comic series called Amanda and Gunn with Image Comics. First, this article deconstructs Cyberzone through the lens of Cultural Prism Theory (CPT). Second, this article situates Cyberzone within the framework of CPT to address Cyberzone 's place within the comic book ecosystem. Finally, this essay offers a close reading of Cyberzone, issues #1–#4, against the backdrop of the intersectional framework Black Queer Identity Matrix . During this process, the researcher demonstrates how Cyberzone is a powerful site of resistant cultural commentary.